2012
DOI: 10.1002/mds.25145
|View full text |Cite|
|
Sign up to set email alerts
|

VPS35 mutation in Japanese patients with typical Parkinson's disease

Abstract: Vacuolar protein sorting 35 (VPS35) was recently reported to be a pathogenic gene for late-onset autosomal dominant Parkinson's disease (PD), using exome sequencing. To date, VPS35 mutations have been detected only in whites with PD. The aim of the present study was to determine the incidence and clinical features of Asian PD patients with VPS35 mutations. We screened 7 reported nonsynonymous missense variants of VPS35, including p.D620N, known as potentially disease-associated variants of PD, in 300 Japanese … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
81
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(81 citation statements)
references
References 26 publications
0
81
0
Order By: Relevance
“…Recently, the p.D620N mutation in the VPS35 gene was identified as a novel cause of autosomal dominant lateonset PD by two research groups [212,213] and five subsequent studies have identified this mutation in PD patients [214][215][216][217]. Moreover, PD-associated defects in RAB7L1 or LRRK2 lead to a deficiency of the VPS35 component of the retromer complex [218].…”
Section: Vps35 (Park17)mentioning
confidence: 99%
“…Recently, the p.D620N mutation in the VPS35 gene was identified as a novel cause of autosomal dominant lateonset PD by two research groups [212,213] and five subsequent studies have identified this mutation in PD patients [214][215][216][217]. Moreover, PD-associated defects in RAB7L1 or LRRK2 lead to a deficiency of the VPS35 component of the retromer complex [218].…”
Section: Vps35 (Park17)mentioning
confidence: 99%
“…Depression seemed to be more common than cognitive impairment. Atypical motor features were not found [12][13][14][15][16][17][18].…”
Section: Clinical Presentationmentioning
confidence: 88%
“…A knock in mouse model suspects that Vps35 D620N allele is a partial-loss-of-function allele and causes an early deficit in dopamine release perhaps before the onset of neurodegeneration [5].…”
Section: Vps35 Mutations In Parkinson´s Disease As a Genetic Causementioning
confidence: 99%
“…Cognitive deterioration seems to be rare in these patients. The protein seems to be involved in endosomal trafficking and recycling of synaptic vesicles, suggesting it may be impaired in this form of PD [14,26].…”
mentioning
confidence: 99%